(3CSQGQ GdMjGI h Gdchf (B:s 29 (3OQGSI YdejI LOjOI dCdeY GdcJGH GdCeQjcjjf (B/s - (3hdje g(B.(3ThQ s; (3SjO QeVGfs ((3GdbGgQI (B:s (3eQcR GdCgQGe ddJQLeI h GdfTQ ,s, 1997)
(3jJJHY gPG GdcJGH QMdI GdYde aj OCH h HdG ghGOI Ydi eQ GdbQhf aj SYjg GdeSJeQ dMd CcKQ GdZGR GdYGde GdeYGUQ eOYGI ddMjQI h jJfbd GdcJGH HGdbGQF NdGd ehVhYGJ eNJdaI ef fTCI Gdchf Gdi fTDA GdMjGI Gdi bVjI GdhYj h GdacQI h GdPGcQI h GdPcGA h cjajI GSJNOGeg Ydi fMh CeKd djfJgj Gdi hVY JUhQGJ Mhd eUjQ GdCQV GdfgGFj h ecGf GdGfSGf aj fXGe Gdchf GdCYXe GJSGYG h GdOQGSGJ GdefThQI h GdJj cJHgG (B29 (3ef GdeY GdcJGH GdGeQcjjf JJSe HGdSghdI h GdSdGdI eY GdJRGe GdObI GdYdejI h GdehVhYjI h JaJM GaGbG QMHI ddJacjQ GdYdej GdNdGb djSJeJY GdLejY HbQGAJgG h jSgd Ydjge GSJjYGHgG QZe GfgG JfGbT bVGjG GdMjGI GdCSGSjIs
Keywords: (3eJfhYGJs; (3Ydhes